2013
DOI: 10.1016/j.neuron.2013.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Patients with Psychosis and a Mouse Model Establishes a Spreading Pattern of Hippocampal Dysfunction and Implicates Glutamate as a Driver

Abstract: SUMMARY The hippocampus in schizophrenia is characterized by both hypermetabolism and reduced size. It remains unknown whether these abnormalities are mechanistically linked. Here, in addressing these questions we used MRI tools that can map hippocampal metabolism and structure in patients and mouse models. In at-risk patients, hypermetabolism was found to begin in CA1 and spread to the subiculum after psychosis onset. CA1 hypermetabolism at baseline predicted hippocampal atrophy, which occured during progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
531
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 496 publications
(604 citation statements)
references
References 62 publications
(88 reference statements)
67
531
6
Order By: Relevance
“…To our knowledge, this is the first application of the ASL method to investigate differences in resting perfusion in a schizotypy group. Given that the study groups only differed on the presence of schizotypal traits, and that hippocampal hyperperfusion has been reported in patients with psychosis (Friston et al, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014, 2015; although see Andreasen et al, 1997; Catafau et al, 1994; Early et al, 1987; Parellada et al, 1994), and in people at CHR of sychosis (Allen et al, 2017, 2016; Schobel et al, 2013), our study findings suggest that increased hippocampal activity (reflected in an elevation of regional perfusion) is also involved in the expression of subclinical psychotic‐like experiences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, this is the first application of the ASL method to investigate differences in resting perfusion in a schizotypy group. Given that the study groups only differed on the presence of schizotypal traits, and that hippocampal hyperperfusion has been reported in patients with psychosis (Friston et al, 1992; Liddle et al, 1992; Malaspina et al, 2004; Pinkham et al, 2011; Schobel et al, 2013, 2009; Talati et al, 2014, 2015; although see Andreasen et al, 1997; Catafau et al, 1994; Early et al, 1987; Parellada et al, 1994), and in people at CHR of sychosis (Allen et al, 2017, 2016; Schobel et al, 2013), our study findings suggest that increased hippocampal activity (reflected in an elevation of regional perfusion) is also involved in the expression of subclinical psychotic‐like experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the clinical or functional correlates of CBF abnormalities along the psychosis spectrum, previous longitudinal studies in CHR individuals reported that (a) elevated hippocampal cerebral blood volume as measured with the contrast agent gandolinium was linked to the risk of later transition to psychosis (Schobel et al, 2013, 2009), (b) increased hippocampal CBF as measured with ASL was subsequently normalized in CHR subjects who remitted from their CHR state (Allen et al, 2016), and (c) hippocampal CBF and medial prefrontal GABA+ concentrations were associated in CHR individuals who subsequently developed a psychotic disorder (Modinos et al, 2018). Although the observation of an increase in resting hippocampal perfusion in HS is consistent with the majority of previous studies in CHR and schizophrenia with a specific focus on the hippocampus, as discussed above, the cross‐sectional nature of the present study prevents investigating whether this finding is prospectively linked to a subsequent emergence of mental health disorders in schizotypy (Cannon et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compensatory adjustments and excitotoxicity associated with long-term GABA dysfunction and neural overactivity may contribute to regional hypoactivity and atrophy characterizing later disease stages (Huang and Mucke 2012;Schobel et al 2013;Anticevic et al 2015), aspects of these chronic disorders not mimicked by acute GABA antagonism.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Prolonged exposure to ketamine in vitro or repeated exposure in vivo increases interleukin-6 production in the brain, which is necessary and sufficient for the activation of NADPH oxidase and the subsequent loss of the GABAergic phenotype of parvalbumin interneurons [29]. Acute ketamine administration (30 mg/kg) produces a gradient of hippocampal hypermetabolism [31]. Moreover, repeated ketamine exposure (16 mg/kg) significantly decreases the parvalbumin-positive cell density relative to a saline-treated control group.…”
Section: Neurotoxic Effects Of Ketaminementioning
confidence: 99%